Lymph node yield and lymph node ratio in oral cavity and oropharyngeal carcinoma: Preliminary results from a prospective, multicenter, international cohort. (August 2020) - Iocca, Oreste; Di Maio, Pasquale; De Virgilio, Armando; Pellini, Raul; Golusiński, Paweł; Petruzzi, Gerardo; Zocchi, Jacopo; Pirola, Francesca; Janczak, Radoslaw; Golusiński, Wojciech; Spriano, Giuseppe; Weinstein, Gregory S.; et al.
Highlights: Lymph Node Yield (LNY) and Lymph Node Ratio (LNR) are emerging prognostic indicators. There is a need of defining the exact values of LNY and LNR according to multiple variables. In 100 patients with oral or oropharynx cancer, LNY and LNR values were obtained and analyzed. The number of dissected neck levels, tumor site, cN positivity and smoking influence the LNY and LNR. Abstract: Objectives: Recently, Lymph Node Yield (LNY) and Lymph Node Ratio (LNR) have emerged as prognostic indicators in head and neck cancer. However, there is a lack of data regarding the LNY and LNR values in the specific neck levels dissected and regarding the factors that influence these values. Materials and methods: Preliminary results of the NCT03534778 trial are reported. LNY and LNR values were estimated for 100 patients with oral or oropharynx carcinoma, from November 1, 2018 to September 30, 2019. Results: Overall, the mean number of lymph nodes retrieved was 34.4 (95% confidence interval [CI] 31.6–37.3). LNY means and CI per single neck level were as follows: level I 5.5 lymph nodes harvested (95% CI 3.5–7.5), level II 15.4 (95% CI 10.6–20.2), level III 8.0 (95% CI 4.6–11.3), level IV 6.3 (95% CI 3.4–9.15), level V 6.3 (95% CI 3.6–9.0). cN+ patients had a higher number of lymph nodes retrieved, odds ratio (OR) 1.2 (95% CI 1.05–1.36). Smokers had less lymph nodes harvested, OR 0.78 (95% CI, 0.71–0.87). Mean LNR was 0.063 (95% CI 0.047–0.078). A multiple regression analysis showed that anatomic site, pN, smoking status and LNY statistically significantly predicted the LNR (p < 0.05) Conclusions: The LNY and LNR values are influenced by various demographic and pathological characteristics of the patient, such as the number of dissected levels, primary site, cN positivity, and smoking status.